MATERNAL AND FETAL COMPLICATIONS OCCURRING IN HEREDITARY THROMBOPHILIA - Janina-Georgiana Nacea (Romanian Journal of Pediatrics, 2017)
Objective. To identify qualitative and quantitative changes involving coagulation factors engaged in maternal and fetal complications, to determine the level of correlation between them, and to highlight the involvement of hereditary thrombophilia among pregnant women. Material and method. The article is based on 92 publications from 1995 to 2017, including a total of 49,127 thrombophilic patients, of whom 1272 were controls, with inclusion criteria as preeclampsia, intrauterine growth retardation, or early or late pregnancy loss. Results. 31 studies based on preeclampsia- demonstrate the involvement of G1691A factor V Leiden gene mutation, G20210A Prothrombin gene mutation and/or C677T and A1298C MTHFR gene mutation as the main factors in the development of this complication. 10 studies focuses on the intrauterine growth restriction place G20210A Factor V Leiden gene mutation, G20210A Prothrombin gene mutation, C677T and A1298C MTHFR gene mutation, protein C and protein S deficiency as the main factors involved. Another 32 studies cite the involvement of factor V Leiden mutation, Prothrombin mutation and MTHFR mutation in the development of early or late pregnancy losses. Conclusion. Based on 92 rigorously selected publications, we were able to demonstrate the relationship between medium/increased risk thrombophilia and pregnancy outcome, especially due to the presence of factor V Leiden gene mutation, Prothrombin gene mutation but also MTHFR gene mutation homozygous status.